The transformation of Virginia, 1740-1790 - Isaac, Rhys (Published for the Omohundro Institute of Early American History and Culture, Williamsburg, Virginia., 1982)
"In this Pulitzer Prize-winning book, Rhys Isaac describes and analyzes the dramatic confrontations - primarily religious and political - that transformed Virginia in the second half of the eighteenth century. Making use of the observational techniques of the cultural anthropologist, Isaac vividly recreates and painstakingly dissects a society in the turmoil of profound inner change."--Jacket